2020
DOI: 10.1080/02615479.2020.1805426
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality and religion: from the court of appeal to the social work classroom

Abstract: This paper critically reviews the case of (R (Ngole) v University of Sheffield [2019]), which concerned a social work student whose professional training was terminated following expression of his religious views about homosexuality on a public social media platform. The student sought a judicial review of this decision on human rights grounds. The High Court dismissed the student's challenge but the Court of Appeal overturned this decision to dismiss on the grounds of proportionality and referred the student … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Westwood [148] has identified disagreement between UK social work practitioners in terms of whether religious disapproval impacts practice with LGBTQ service users. Some practitioners believe it is possible to separate off personal views, including those based on religious beliefs, while others believe it is not possible and that, indeed, religious disapproval of LGBTQ people and their lives are contrary to social work values [149]. These findings echo previous research on social work training from the US, where similar divided views prevail [150][151][152][153][154][155].…”
Section: Older Lgbtq People Care and Religionsupporting
confidence: 67%
“…Westwood [148] has identified disagreement between UK social work practitioners in terms of whether religious disapproval impacts practice with LGBTQ service users. Some practitioners believe it is possible to separate off personal views, including those based on religious beliefs, while others believe it is not possible and that, indeed, religious disapproval of LGBTQ people and their lives are contrary to social work values [149]. These findings echo previous research on social work training from the US, where similar divided views prevail [150][151][152][153][154][155].…”
Section: Older Lgbtq People Care and Religionsupporting
confidence: 67%
“…Many of the studies recommended promoting reflective dialogue among religious students and practitioners (Acker, 2017; Aihiokhai, 2021; Dessel, 2014; Joslin et al., 2016; Vinjamuri, 2017). Such initiatives would necessitate educators feeling sufficiently skilled and confident to promote reflective dialogue, and to explore issues with those students who may be experiencing tensions between their personal beliefs and professional requirements, including in relation to LGBTQ‐inclusive and affirmative practice (Mason et al., 2020). This is particularly important, given that several studies have suggested that highly religious students/staff can be resistant to taking a critical/reflective approach to their religious beliefs, and to associated training/education initiatives (Dessel et al., 2012; Hardacker et al., 2014; Vinjamuri, 2017; Westwood & Knocker, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the first, a doctor unsuccessfully claimed unfair dismissal for refusing, on the grounds of his religious beliefs, to refer to trans people by the pronouns with which they identified 1 . In the second case, 2 a conservative Christian social work student from Cameroon who made homophobic comments on his Facebook page, quoting from religious texts which described people who engage in same‐sex relations as ‘an abomination’, successfully appealed expulsion from his course because of them (Mason et al., 2020). In the third case, 3 an evangelical Christian fostering and adoption agency challenged a UK regulatory requirement that it ceases its policy to only employ staff and volunteers who are evangelical Christians and who ‘refrain from “homosexual behaviour”’ 4 and to only recruit carers who are ‘evangelical married heterosexual couples of the opposite sex’ 5 .…”
Section: Introductionmentioning
confidence: 99%
“…One social work academic noted that critical reflection and examination of one's own prejudices is an essential prerequisite for preparing students for curious and assertive practice, and that unlearning for some students has to take place in safe spaces given what personal prejudices or ignorance they may bring into their practice. Again, the unaddressed religious beliefs of learners were mentioned as a barrier (Mason, Cocker, & Hafford-Letchfield, 2020).…”
Section: Investing and Developing The Knowledge And Skills Of Professionals: Qualifying And Postqualifying Education And Ongoing Work-basmentioning
confidence: 99%